INFORMATION-MEASURING SYSTEM WITH TIME REPRESENTATION OF INFORMATION BASED ON FIBER-OPTICAL SENSORS - Shabatura, Yury; Zelena, Olga (Scientific Works of Vinnytsia National Technical University, 2015)
Expedience of fiber-optic IMS usage functioning on the basis of interval method of measurement is substantiated, realization of circular structure of IMS, using one communication line to which sensors, able to perceive code sampling signals for each separate sensor for fiber-optic IMS is considered. The given approach can be realized by means of spatial division of optic signals and transition from continuous to pulse operation mode.